2014
DOI: 10.1124/mol.113.090076
|View full text |Cite
|
Sign up to set email alerts
|

Nanomolar Bifenthrin Alters Synchronous Ca2+Oscillations and Cortical Neuron Development Independent of Sodium Channel Activity

Abstract: Bifenthrin, a relatively stable type I pyrethroid that causes tremors and impairs motor activity in rodents, is broadly used. We investigated whether nanomolar bifenthrin alters synchronous Ca 21 oscillations (SCOs) necessary for activity-dependent dendritic development. Primary mouse cortical neurons were cultured 8 or 9 days in vitro (DIV), loaded with the Ca 21 indicator Fluo-4, and imaged using a Fluorescence Imaging Plate Reader Tetra. Acute exposure to bifenthrin rapidly increased the frequency of SCOs b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…In this regard, in addition to the decreased glutamate and calcium levels identified after postnatal exposures (Carloni and others 2012; Carloni and others 2013), in cultures of neonatal hippocampal neurons, the activity of glutamatergic neuronal networks and the spontaneous release of glutamate in synapses are decreased (Meyer and others 2008) and, recently, a NMDA receptor-mediated mechanism was suggested to play a role in PIs neurotoxic actions during development. Cao and collaborators (Cao and others 2014) demonstrated that, in primary cultures of neonatal cortical neurons, bifenthrin, at concentrations well below those that delay sodium channel inactivation and affect sodium current, alters spontaneous synchronized calcium oscillations that are essential for normal neuronal development (Dolmetsch and others 1998; Wayman and others 2006) and increases phosphorylated CREB and activity-dependent dendritic growth. These effects are partially suppressed by NMDA receptors antagonists (Cao and others 2014).…”
Section: Pyrethroids (Pis)mentioning
confidence: 99%
“…In this regard, in addition to the decreased glutamate and calcium levels identified after postnatal exposures (Carloni and others 2012; Carloni and others 2013), in cultures of neonatal hippocampal neurons, the activity of glutamatergic neuronal networks and the spontaneous release of glutamate in synapses are decreased (Meyer and others 2008) and, recently, a NMDA receptor-mediated mechanism was suggested to play a role in PIs neurotoxic actions during development. Cao and collaborators (Cao and others 2014) demonstrated that, in primary cultures of neonatal cortical neurons, bifenthrin, at concentrations well below those that delay sodium channel inactivation and affect sodium current, alters spontaneous synchronized calcium oscillations that are essential for normal neuronal development (Dolmetsch and others 1998; Wayman and others 2006) and increases phosphorylated CREB and activity-dependent dendritic growth. These effects are partially suppressed by NMDA receptors antagonists (Cao and others 2014).…”
Section: Pyrethroids (Pis)mentioning
confidence: 99%
“…It is one of the most potent commercialized pyrethroids to date, with an oral lethal dose-50 (LD 50 ) values of 53 mg/kg in female rats and 70 mg/kg in male rats (Cao et al 2014). Pyrethroids slow the closing of sodium channel gates, following an initial influx of sodium during the depolarizing phase of an action potential, which results in a prolonged sodium tail current (Dubey, Khan, and Raina 2013;Yang and Li 2015).…”
Section: Introductionmentioning
confidence: 99%
“…These recent data suggest that excitotoxic chemicals that promote seizures by engaging distinct biochemical targets might be resolved by how they differentially influence neuronal Ca 21 dynamics and SCO. Importantly, acute alterations in SCO patterns could provide valuable leads to identify downstream signaling mechanisms that affect longterm changes in neuronal development and neuropathology (Cao et al, 2014b).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, this approach is capable of high throughput discovery of anticonvulsants. The method also lends itself for studies of developmental neurotoxicants (Cao et al, 2014b) and those that promote neurodegeneration.…”
mentioning
confidence: 99%